Modelling the Complete Molecular Weight Distribution in Chain Growth Polymerizations. (5th July 2016) - Infante-Martínez, Ramiro; Saldívar-Guerra, Enrique; Pérez-Camacho, Odilia; García-Zamora, Maricela; Comparán-Padilla, Víctor
ABSTRACT: This work shows the development of several models for chain-growth polymerizations that admit the direct calculation of the complete molecular weight distribution of the polymer. The direct and complete calculation implies that no statistical mean values are employed as in the moments method neither numerical approximations like in the minimum-squared based methods. The free radical polymerization of ethylene (LDPE) and the coordination via metallocenes polymerization of ethylene (HDPE) are taken as examples for analysis. In the free radical polymerization case, the conventional scheme for chain-growth polymerization is adopted, with steps for initiation, propagation, chain transfer to small species and the additional step of chain transfer to dead chains [1]. The kinetic parameter are obtained from the open literature. Two kind of reactors were modelled: batch and continuous stirred tank reactor. For this last case, a simulation strategy was considered in which the run started from an initial known population of dead chains. Results show that typical non-linear polymerization profiles for the molecular weight distribution are obtained. For the coordination polymerization of ethylene via metalocenes, the standard coordination model was employed [2]. A two-site catalyst was considered and kinetic parameters reported in the open literature were used. For this study an experimental program in a lab-scale reactor was undertaken in order to obtain modelling data [3]. Results show that the standard model adequately reproduces the experimental data in the kinetic and molecular attributes of the polymer.